Negative Correlation between Lipid Content and Antibiotic Activity in Streptomyces: General Rule and Exceptions - Michelle David; Clara Lejeune; Sonia Abreu; Annabelle Thibessard; Pierre Leblond; Pierre Chaminade; Marie-Joelle Virolle (MDPI AG, 2020)
Streptomycetes are well known antibiotic producers and are among the rare prokaryotes able to store carbon as lipids. Previous comparative studies of the weak antibiotic producer Streptomyces lividans with its ppk mutant and with Streptomyces coelicolor, which both produce antibiotics, suggested the existence of a negative correlation between total lipid content and the ability to produce antibiotics. To determine whether such a negative correlation can be generalized to other Streptomyces species, fifty-four strains were picked randomly and grown on modified R2YE medium, limited in phosphate, with glucose or glycerol as the main carbon source. The total lipid content and antibiotic activity against Micrococcus luteus were assessed for each strain. This study revealed that the ability to accumulate lipids was not evenly distributed among strains and that glycerol was more lipogenic than glucose and had a negative impact on antibiotic biosynthesis. Furthermore, a statistically significant negative Pearson correlation between lipid content and antibiotic activity could be established for most strains, but a few strains escape this general law. These exceptions are likely due to limits and biases linked to the type of test used to determine antibiotic activity, which relies exclusively on Micrococcus luteus sensitivity. They are characterized either by high lipid content and high antibiotic activity or by low lipid content and undetectable antibiotic activity against Micrococcus luteus. Lastly, the comparative genomic analysis of two strains with contrasting lipid content, and both named Streptomyces antibioticus (DSM 41,481 and DSM 40,868, which we found to be phylogenetically related to Streptomyces lavenduligriseus), indicated that some genetic differences in various pathways related to the generation/consumption of acetylCoA could be responsible for such a difference.